2015
DOI: 10.1186/s13071-015-0924-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex fluorescence immunological assay for the simultaneous detection of antibodies against Cooperia oncophora, Dictyocaulus viviparus and Fasciola hepatica in cattle

Abstract: BackgroundA major constraint for the effective control and management of helminth parasites is the lack of rapid, high-throughput, routine diagnostic tests to assess the health status of individual animals and herds and to identify the parasite species responsible for these helminthoses. The capability of a multiplex platform for the simultaneous detection of three pasture associated parasite species was evaluated and compared to existing ELISAs.MethodsThe recombinant antigens 14.2 kDa ES protein for Cooperia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…In the present study, the overall F. hepatica seroprevalence was 28.7% (454/1,584), which was lower than that reported in yaks in Xinghai tested by autopsy method [9,10], cattle in Switzerland [14], Poland [14], Australia [15], Ireland [16], and Vietnam [17] examined by ELISA, but higher than that of cattle in Spain [5] and Denmark [18], cow in Germany [19] tested by ELISA. It has been demonstrated that F. hepatica infection mainly occurs in cattle [20] and goats [20], otherwise, F. gigantica usually infect water buffaloes.…”
contrasting
confidence: 69%
“…In the present study, the overall F. hepatica seroprevalence was 28.7% (454/1,584), which was lower than that reported in yaks in Xinghai tested by autopsy method [9,10], cattle in Switzerland [14], Poland [14], Australia [15], Ireland [16], and Vietnam [17] examined by ELISA, but higher than that of cattle in Spain [5] and Denmark [18], cow in Germany [19] tested by ELISA. It has been demonstrated that F. hepatica infection mainly occurs in cattle [20] and goats [20], otherwise, F. gigantica usually infect water buffaloes.…”
contrasting
confidence: 69%
“…Karanikola et al. () developed a bead‐based assay using fluorescence detection (xMAP® technology) for the simultaneous detection of antibodies against F. hepatica , Cooperia oncophora and Dictyocaulus viviparus in cattle serum samples. This platform was shown to be highly sensitive and specific in comparison with existing serological and coprological diagnostic techniques.…”
Section: Diagnosismentioning
confidence: 99%
“…The coupling was carried out as described by Karanikola et al [16]. Twenty μL of magnetic beads (about 1.25 × 10 6 beads) was transferred to a low-adsorption reaction tube and placed into the magnetic separator for 30 s, followed by centrifugation to remove the supernatant.…”
Section: Coupling Of Antigens To Fluorescent Beadsmentioning
confidence: 99%